Understanding Students’ Proportional Reasoning through Contextual Tasks in RME: A Qualitative Perspective - etmy, desventri; amalia putri , prismadian; yandi raharjo, Eko; susanta, agus; yensy astuty, nurul (Journal of Mathematics and Applied Statistics, 2025)
This study aims to describe students’ mathematical reasoning processes within the framework of Realistic Mathematics Education (RME), particularly focusing on how learners develop proportional and logical reasoning through contextual tasks. Using a qualitative case study design, the research involved classroom observations, task-based interviews, and analysis of students’ written work collected from two purposively selected university students. Data were examined through thematic analysis to identify patterns of reasoning related to multiplicative strategies, symbolic manipulation, and the use of contextual or visual representations. The findings indicate that both students demonstrated strong procedural and symbolic proficiency, especially in applying logical laws and performing formal transformations; Student A showed consistent vertical mathematization, while Student B provided partial conceptual explanations but lacked systematic justification. However, neither student exhibited meaningful horizontal mathematization, contextual interpretation, nor the use of emergent models characteristic of RME-based learning. Their reasoning predominantly reflected imitative-procedural approaches rather than creative or relational reasoning, suggesting that their learning experiences did not sufficiently support guided reinvention or conceptual development through realistic contexts. These results highlight the need for instructional designs that integrate contextual tasks, visual models, and scaffolding aligned with RME principles to foster deeper conceptual understanding and more flexible reasoning. Keyword : Proportional Reasoning; Realistic Mathematics Education (RME); Mathematical Reasoning.